Determinação das propriedades mecânicas das placas de OSB e do comportamento da ligação entre as placas de OSB e o reticulado de aço do sistema Ligth Steel Framing - Sabrina Moreira Villela (2015)
This research aims an experimental study to determine the mechanical properties of Oriented Strand Board (OSB) and the behavior of the link between OSB and the building system Light Steel Framing (LSF). 360 flexure tests were performed on specimens for determination of OSB boards Resilient Modulus and Stress Rupture with different thicknesses manufactured in Brazil. 12 sliding tests were also carried out ("push-test") in LSF, these models consist of OSB boards fixed by means of self-tapping screws the profile of crosslinked formed galvanized steel for determining the behavior of this binding subsystem. The results of 3 points flexure tests showed that the obtained results for the modulus of elasticity and the breakdown voltage varies according to the thickness of the OSB boards; also showed that the proximity of the results by the coefficient of variation, is as bigger as the thickness, higher is the range of the test, up to 48 times the nominal thickness of the board. The sliding tests can be obtained important results related to rigidity and link capacity of OSB board with the metal lattice.